2004
DOI: 10.1111/j.1399-0004.2004.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for single origins of 35delG and delE120 mutations in the GJB2 gene in Anatolia

Abstract: Eighteen different sequence changes, including three novel alterations, were detected in GJB2, encoding connexin 26, in 371 Turkish probands with non-syndromic sensorineural hearing loss. Two frequently detected mutations, 35delG and delE120, were shown to have single origins based on the conserved genotypes of two closely linked microsatellite and five single nucleotide polymorphism markers. Carrier frequencies of 35delG and delE120 in Egypt and Turkic populations of the Near East provide insights about the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
35
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 22 publications
8
35
0
1
Order By: Relevance
“…When the 35delG mutation of the GJB2 gene is mutant in both alleles, it causes SNHL. In NSSNHL patients with familial autosomal recessive inheritance, the rate of 35delG homozygosity was reported as 17.5%-21.7%, and the rate of heterozygous mutation was reported as 1.9%-4.3% (18,25,26). Regarding the familial history of patients in the study group of our study, congenital NSSNHL was determined at least in one person in the families of 18.3% of patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…When the 35delG mutation of the GJB2 gene is mutant in both alleles, it causes SNHL. In NSSNHL patients with familial autosomal recessive inheritance, the rate of 35delG homozygosity was reported as 17.5%-21.7%, and the rate of heterozygous mutation was reported as 1.9%-4.3% (18,25,26). Regarding the familial history of patients in the study group of our study, congenital NSSNHL was determined at least in one person in the families of 18.3% of patients.…”
Section: Discussionmentioning
confidence: 59%
“…Nearly 70% of the pathological GJB2 mutations seen in Europe, North America, and Mediterranean societies comprise 35delG (16). It has been reported that the incidence frequency of the 35delG mutant allele is in the range of 5% to 53% in different cities of our country (17,18). In studies conducted, GJB2 mutations, other than 35delG, were found at high frequency for different ethnic groups.…”
Section: Discussionmentioning
confidence: 83%
“…The second fact is that c.235delC, the GJB2 mutation that most frequently causes autosomal recessive hearing impairment (MIM * 121011) in Asia has a frequency of 3.4-13.9% [12][13][14], far below the 35% of autosomal recessive hearing impairment caused by c35deG in southern Europe [6]; even when we are talking about two ancient mutations that could be considered contemporaneous [60][61][62]64] and its carrier frequencies are remarkably similar [17]. This makes us suspect that perhaps p.Val27Ile has some protecting effect against the emergence of GJB2 pathogenic mutations in cis configuration with this polymorphism; which is supported by the very low frequency of this kind of haplotype (p.Val27Ile; pathogenic mutation) [14,29,59]. The third fact is that p.Val27Ile seems to be capable of compensating for the decreased activity of p.Glu114Gly in heterotypic hemichannels of GJB2 (compound by p.Val27Ile and p.Glu114Gly), as have been demonstrated by in vitro tests [67].…”
Section: Discussionmentioning
confidence: 95%
“…This low frequency could be due to the many ethnically distinct populations that immigrated into Turkey from the Paleolithic Era, mainly during the past 10,000 years [27,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in 1999, and in a study, its frequency was reported to be approximately 1% [26] . In two studies from our country, it was reported that delE120 mutation is the second most common mutation following 35delG, and that its allele frequency was approximately 2% [27,28] . In our study group, frequency of this mutation was 1.4%.…”
Section: Discussionmentioning
confidence: 99%